2004
DOI: 10.1002/ijc.20436
|View full text |Cite
|
Sign up to set email alerts
|

Inherited predisposition to early onset lung cancer according to histological type

Abstract: The role of hereditary factors in lung cancer is less well understood than in many other human neoplastic diseases. We used a nation-wide family dataset to search for evidence for a genetic predisposition in lung cancer. The Swedish Family-Cancer Database includes all Swedes born in 1932 and later (0-to 68-year-old offspring) with their parents, totaling over 10.2 million individuals. Cancer cases were retrieved from the Swedish Cancer Registry up to year 2000. Standardized incidence ratios (SIR) and 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 39 publications
(39 reference statements)
5
45
0
1
Order By: Relevance
“…Bromen et al (2000) reported a 4.75-fold increase in risk of lung cancer among relatives of probands who were diagnosed with lung cancer before the age of 50 years. Li and Hemminki (2004) used a Swedish register of families to estimate standardised incidence ratio for offspring and siblings of cases of lung cancer, and found a substantially increased risk of disease before the age of 50 years in relatives of cases. In an alternative analysis to quantify the lifetime risk of lung cancer in first-degree relatives of earlyonset cases diagnosed before the age of 50 years, Cote et al (2005) reported a 1.91-fold increased risk of lung cancer for relatives of early-onset cases compared to affected relatives in a control population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromen et al (2000) reported a 4.75-fold increase in risk of lung cancer among relatives of probands who were diagnosed with lung cancer before the age of 50 years. Li and Hemminki (2004) used a Swedish register of families to estimate standardised incidence ratio for offspring and siblings of cases of lung cancer, and found a substantially increased risk of disease before the age of 50 years in relatives of cases. In an alternative analysis to quantify the lifetime risk of lung cancer in first-degree relatives of earlyonset cases diagnosed before the age of 50 years, Cote et al (2005) reported a 1.91-fold increased risk of lung cancer for relatives of early-onset cases compared to affected relatives in a control population.…”
Section: Discussionmentioning
confidence: 99%
“…Biological theory and the experience of other cancers, including breast (Hopper et al, 1999), pancreas (James et al, 2004) and colon (Strate and Syngal, 2005), suggest that tumours associated with genetic factors tend to occur early in life. Numerous lung cancer studies have investigated the numbers of affected relatives and ageat-onset, with greatest risk seen in families with early-onset lung cancer compared with those whose onset of lung cancer occurred at older ages (Kreuzer et al, 1998;Bromen et al, 2000;Gauderman and Morrison 2000;Li and Hemminki, 2004;Cote et al, 2005). However, information on familial risk by age-at-onset of both the proband and the affected relatives is rare in lung cancer studies.…”
mentioning
confidence: 99%
“…7,20 Thus in covering familial cases, by definition, the present subjects were sensitive to tobacco-related lung and other cancers, increasing the likelihood of observing effects. The SIRs measured between parental lung cancers and any offspring cancers would be elevated if there were genuine heritable causes for cancer susceptibility between the 2 sites.…”
Section: Discussionmentioning
confidence: 94%
“…It is likely that the familial risk for lung cancer, which is about 2.0, is partially explained by shared smoking habits among family members. 7 Thus, in analyzing cancer risks for offspring, we have no possibility to exclude the effects of their active smoking. However, we use age of onset and the relative magnitude of the effect in relation to lung cancer risks as reference points for possible inferences about cancer causation in offspring.…”
mentioning
confidence: 99%
“…Even so, the role of this oncogene in the development of lung caner remains nebulous. In this regard, the findings reported by Li and Hemminki [68] may shed some light on this issue in that they describe an inherited predisposition to early-onset lung cancer due to mutations in the EGFR oncogene in a familial clustering with several cases of NSCL. KRAS belonging to the EGFR pathway genes is known to have mutated into various kinds of human tumors.…”
Section: Cell-free Circulating Dna As a Diagnos-tic Marker In Lung Camentioning
confidence: 92%